PENYULUHAN MATERI PEMBUATAN KEMASAN KREATIF DALAM PROGRAM KKN TEMATIK MANDIRI DI DESA CIPANJALU - Aryani, Dewi Isma; Manurung, Rosida Tiurma (Abdi Seni, 2024)
Universitas Kristen Maranatha has managed the Indonesian University thematic community service program (KKN)annually. Thematic KKN at Cipanjalu Village, Bandung Regency, was during the even semester of 2022/2023, withthirteen meetings and ten work programs. The 9th meeting of the thematic KKN featured MSME actors in CipanjaluVillage, with the topic “Tips and Tricks for Making Product Packaging Creatively.” The group consists of teachingstaff and 14 students from different departments of Universitas Kristen Maranatha for the thematic KKN at CipanjaluVillage, Bandung Regency. The seventh work program in this community service focuses on helping to createinventive and ecologically friendly product packaging. A creative, autonomous, and environmentally responsiblecommunity is developing through the work program at thematic KKN in Cipanjalu Village, which is intended toboost the economy and progress MSMEs by implementing efficient technologies.